Ecografia modo-b e doppler na avaliação das artérias epigástricas superficiais no neoplasma mamário canino - Bortolini, Carlos Eduardo (2018)
The objectives of this study were to evaluate the hemodynamics of cranial and caudal superficial epigastric arteries on Doppler ultrasound, identify the ultrasound characteristics of the vessels and of the tumor texture, measure the levels of vascular endothelial growth factor (VEGF) and interleukin-8 of canine patients with mammary carcinomas, and predict the biological behavior of mammary carcinoma based on the hemodynamic variations of superficial epigastric arteries in early cancer stages. For this, the flow velocity and resistive index of the cranial and caudal superficial epigastric arteries of 63 female canines were evaluated by Doppler ultrasound. The mammary tumor group comprised 43 canines with the histopathological diagnosis of mammary carcinoma, whereas the control group comprised 20 healthy canine. The vascular dynamics was significantly different between the two groups, and the number of tumor lesions affected the vessel flow rate. In addition, the echotexture and presentation and distribution of the vessels affected the resistive index in the mammary carcinoma group. Fifty other female canines were divided into two groups (13 healthy canines and 37 canines with mammary carcinoma) to evaluate the clinical usefulness of the serum measurement of VEGF, interleukin-8, and estradiol, combined with ultrasound examination of malignant tumors. The results demonstrated the strong correlation of echotexture with interleukin-8 levels and the positive correlation between tumor vessel flow rate and VEGF levels. These findings indicate a relationship between the tumor environment and expression of interleukin-8 as well as the effect of flow dynamics on VEGF levels. Finally, 142 mammary nodules or masses were evaluated by ultrasound to assess tumor flow dynamics and differentiate between benign and malignant mammary tumors. The biodynamics of internal vessels was significantly different between benign and malignant tumors, with systolic and diastolic velocities varying according to tumor size and echotexture. Therefore, the joint evaluation of tumor size and texture and of the flow velocity of internal tumor vessels may be useful for differentiating between benign and malignant mammary tumors. The present study presents an important application of ultrasound imaging in veterinary oncology and demonstrates the effect of hemodynamics on cranial and caudal superficial epigastric arteries, evidenced by Doppler ultrasound, in canine mammary carcinoma, particularly when associated with the analysis of tumor size and texture, and of the presentation and distribution of tumor vessels. These findings confirm that mechanical factors of tumors interfere in the hemodynamics of superficial epigastric arteries. These results indicate the importance of evaluating the arteries that irrigate the affected mammary chain together with other factors predictive of tumor malignancy, including tumor size, heterogeneous echotexture of the tumor stroma, heterogeneous presentation and complex distribution of tumor vascularization, and serum levels of VEGF and interleukin-8.